Assessment of analytical and numerical models on experimental data for the study of single-phase natural circulation dynamics in a vertical loop. (27th April 2017) - Luzzi, L.; Misale, M.; Devia, F.; Pini, A.; Cauzzi, M.T.; Fanale, F.; Cammi, A.
Highlights: Analytical/numerical models for natural circulation loop dynamics are assessed against experiments. Thermal Inertia (TI) of piping materials influences Natural Circulation Loop (NCL) behaviour. The Heat-Exchanger (HE) section needs an accurate modelling. If TI and HE are properly modelled, 1D and CFD simulations are able to catch the L2 NCL dynamics. The SST k – ω model can be a good choice for the CFD turbulence treatment in the considered NCL. Abstract: In this paper, semi-analytical and numerical models developed in our previous works to study the dynamic behaviour of natural convection are assessed against the experimental data obtained by means of the L2 Natural Circulation Loop (NCL) of DIME-Tec Labs (University of Genoa). As for the experimental campaign, reference is made to a set of nine experiments performed using water as working fluid and providing a thermal power of 2 kW. This set of data is firstly adopted for the validation of a semi-analytical linear analysis tool aimed at studying the asymptotic behaviour of NCLs through the definition of dimensionless stability maps. Then, two different numerical models (adopted in our previous work to confirm the linear analysis) are assessed, namely an Object-Oriented (O-O) one-dimensional model and a three-dimensional Computational Fluid Dynamics (CFD) model. In this regard, the O-O model represents a fast tool for the evaluation of the most important quantities, such as the velocity and the temperature fields in the loop along the axial coordinate. On the other hand, the CFD tool, which is intended as a support to the 1D analysis, is characterised by a high computational burden, but allows highlighting interesting 3D spatial effects. The validation of these tools is not secondary with respect to that of the stability maps. Actually, the numerical approach is fundamental to study the time-dependent behaviour of both stable and unstable natural circulation regimes, for which the stability maps do not provide information. As for the achieved results, the developed models are able to catch the behaviour of the experimental data. In particular, this outcome is possible if an accurate modelling of both the heat-exchanger section and the piping thermal inertia is considered.